The extrinsic factors important to the homeostasis of allergen-specific memory CD4 T cells - Choi, Aryeong; Jung, Yong Woo; Choi, Hanbyeul (Frontiers in Immunology, 2022)
Memory T cells, which are generated after the primary immune response to cognate antigens, possess unique features compared to naïve or effector T cells. These memory T cells are maintained for a long period of time and robustly reactivate in lymphoid or peripheral tissues where they re-encounter antigens. Environments surrounding memory T cells are importantly involved in the process of the maintenance and reactivation of these T cells. Although memory T cells are generally believed to be formed in response to acute infections, the pathogenesis and persistence of chronic inflammatory diseases, including allergic diseases, are also related to the effector functions of memory CD4 T cells. Thus, the factors involved in the homeostasis of allergen-specific memory CD4 T cells need to be understood to surmount these diseases. Here, we review the characteristics of allergen-specific memory CD4 T cells in allergic diseases and the importance of extrinsic factors for the homeostasis and reactivation of these T cells in the view of mediating persistence, recurrence, and aggravation of allergic diseases. Overall, this review provides a better understanding of memory CD4 T cells to devise effective therapeutic strategies for refractory chronic inflammatory diseases.